Metabolic profiling and gene expression analysis reveal the quality deterioration of postharvest toon buds between two different storage temperatures - Zhao, Hu; Shen, Cheng; Hao, Qingping; Fan, Mingqin; Liu, Xiaoli; Wang, Juan (Frontiers in Plant Science, 2023)
Toon buds, a popular woody vegetable, contain large amounts of nutrients. However, toon buds have strong respiratory metabolism after harvest and are highly prone to decay, resulting in quality deterioration. Low-temperature is an effective for inhibiting postharvest senescence of toon buds. GC-MS combined with quantitative real-time PCR was used to elucidate toon bud deterioration mechanism after harvest by analyzing the difference in the relative contents of primary metabolites, chemicals composition, and the expression of key genes associated with metabolic pathways in toon buds between low-temperature and room temperature storages for 72 h. Results showed that the ethylene synthesis in toon buds accelerated under room temperature storage, resulting in significant changes in the primary metabolic pathway. The catabolism of amino acids, fatty acids, and cell membrane phospholipids was accelerated, and the gluconeogenesis synthesis was strengthened. Moreover, the sucrose synthesis was increased, the glycolysis and TCA cycle were broken down, and the pentose phosphate pathway was vigorous. These phenomena resulted in a considerable accumulation of organic acids. Moreover, the secondary metabolic reaction related to the formation of aromatic compounds and active side reactions (transamination, deamination, dehydrogenation and oxidation) produced various toxic compounds. This work provided a comprehensive understanding of the metabolic regulation of toon buds in response to room temperature storage during postharvest senescence and quality deterioration.